Invisible - Gonzalez, Christina Diaz, 1969- (Graphix, 2022)
When five middle school kids are thrown together to complete community service hours in the local cafeteria, Miguel, Dayara, Sara, Nico, and George, who come from different backgrounds, learn that they've been put together because administrators see them only as Latinx. However, when they learn that someone is in desperate need of help, the five band together to help in the best way they know how and later must explain themselves to skeptical school officials.